Structural Characteristics of Knowledge Exchange in Innovation Networks - Michael Rothgang; Bernhard Lageman (International Journal of Computational Economics and Econometrics, 2018)
While there is a large pool of assured knowledge on various general dimensions of struc-tures and dynamics of innovation networks, there are basic structural features that should attain more attention in future network research. Our contribution concentrates on three key structural characteristics: (i) kind of actors, (ii) contexts and (inter-) organizational environments of networks and (iii) modes and contents of knowledge exchange. We dis-cuss the role of these structural characteristics at the example of research material drawn from an accompanying evaluation of the German 'Leading-Edge Clusters Competition'. Major results are: Innovation network actors present themselves in a highly heterogeneous manner; the relevant spectrum reaches from utmost complex organizations to single indi-viduals. Networks are embedded in different sectoral, organizational and situational con-texts. In many cases, already the delimitation of the relevant network is a challenge for innovation researchers. Knowledge exchange uses different channels and presents itself as context-dependent combination of formal and tacit elements, of (relative) openness and restraint of the acting individuals and organizations.
Keywords: 330; Innovation Networks; Actors; Knowledge Exchange; Cluster Organization; Cluster Policy